Unveiling the remarkable diversity of the genus Hypotrichomonas (Parabasalia: Hypotrichomonadidae) in cockroaches (Blattodea, excluding Isoptera) - Kotyk, Michael; Kotyková Varadínová, Zuzana; Hrubá, Pavla; Čepička, Ivan (Protist, 2025)
Parabasalid hindgut symbionts of the xylophagous Isoptera/Cryptocercus lineage (Blattodea: Blattoidea) have been attracting the interest of biologists for decades. However, the parabasalids from other cockroaches (Blattodea excluding Isoptera) remain largely unstudied. The genus Hypotrichomonas, along with genus Trichomitus, belongs to the small parabasalid order Hypotrichomonadida. So far, ten valid Hypotrichomonas species have been described from animals, both vertebrates and invertebrates. Here we have uncovered an extensive diversity of this genus in cockroaches. We have obtained 72 isolates from 41 cockroach species and one from a water-filled tree hole. Using a combination of light-microscopic morphology of protargol-stained cells, scanning electron microscopy, and a phylogenetic analysis of SSU rRNA gene, we show that our strains represent multiple novel Hypotrichomonas species, and we formally describe seven of them. Our data show that the evolutionary center of the genus likely lies in cockroaches. Moreover, the new evolutionary lineages of Hypotrichomonas from cockroaches show a high degree of host specificity.
Keywords: Taxonomy; biodiverzita; fylogeneze; švábi; Morphology; DNA, Ribosomal; Molecular Sequence Data; Parabasalidea; sekvenční analýza DNA; DNA, Protozoan; Trichomonads; ribozomální DNA; protozoální DNA; Sequence Analysis, DNA; RNA ribozomální 18S; Animals; zvířata; RNA, Ribosomal, 18S; Cockroaches; Biodiversity; Phylogeny; molekulární sekvence - údaje; SEM